Prevalence of care for road traffic accident victims during the COVID-19 pandemic - Rayff Rodrigues dos Santos; Luma Vanessa Camberimba de Alencar; Maria Zélia de Araújo Madeira; Ana Maria Ribeiro dos Santos; Joelita de Alencar Fonseca Santos; Ellen Eduarda Santos Ribeiro (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2023)
Objective: to analyze the prevalence of traffic accidents attended at an urgent and emergency referral hospital, in the context of the COVID-19 pandemic. Methods: cross-sectional study with a sample of 364 adult victims of traffic accidents, aged between 18 and 60 years, of both sexes. A sociodemographic characterization form and accident characteristics were used to collect data. The variables were analyzed using descriptive statistics, bivariate analysis, and Fisher's Exact test, with a significance level of 5% (p<0.05). Results: In the sample, there was a predominance of male patients (77.1%), drivers (71.1%), involving motorcycle (68.6%) and without the use of protective equipment (73.3%). The predominant injuries in accidents were fractures (70.8%). Conclusion: Although the prevalence of emergency care for traffic accident victims during the COVID-19 pandemic decreased from 0.77% (2019) to 0.34% in 2020, it was noticed that the variables still remained predominant. Therefore, the findings comprise an important tool for prevention and health promotion policies, aiming at reducing deaths, injuries and disabilities.